2023
DOI: 10.1037/aap0000262
|View full text |Cite
|
Sign up to set email alerts
|

Colonial mentality, racism, and depressive symptoms: Asian Indians in the United States.

Abstract: Colonial mentality is one of the most damaging outcomes of colonization where colonizers are perceived as superior compared to the culture, society, and heritage of colonized people (David & Okazaki, 2006a;Martín-Baro ´, 1994). For Asian Indians (AIs), colonial mentality may manifest as cultural shame and inferiority, preference for lighter skin color, discriminating against less-Americanized Indians (e.g., speaking with an Indian accent), and feeling indebted for colonization. The goal of our study was to app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…While we can extrapolate estimates for Asian Indians in the U.S. based on studies on Asian Indians living in India or on Asian Americans, the Asian Indian community in the U.S. carries its own unique set of socio-cultural and immigration-related considerations that may influence impacts and prevalence rates of traumatic experiences. Examples of such socio-cultural and immigration-related considerations include prejudicial experiences, racial discrimination, and marginalization (e.g., anti-Muslim sentiment post 9/11, anti-Asian sentiment during the COVID-19 pandemic, “Dot Buster” incidents); stress due to the immigration process; economic stressors (e.g., financial responsibilities for accompanying families, need to send money to family in India); communication and language barriers; acculturation stressors (e.g., cultural shock); colonial mentality; stress due to ethnic identity conflicts; and the lack of knowledge about local healthcare institutions and policies (Chandra et al, 2016; Falicov et al, 2020; Inman, 2006; Inman, Yeh, et al, 2007; Jin et al, in press; Lee & Lu, 1989; Nadimpalli et al, 2016; Nikalje & Çiftçi, 2021; Tewari et al, 2003; Tummala-Narra & Deshpande, 2018; Tummala-Narra et al, 2011). Indeed, experiences of racism and discrimination contribute to poor psychological (Kaduvettoor-Davidson & Inman, 2013) and physical (Utsey et al, 2000) health.…”
Section: Traumatic Experiences and Posttraumatic Stress Disordermentioning
confidence: 99%
“…While we can extrapolate estimates for Asian Indians in the U.S. based on studies on Asian Indians living in India or on Asian Americans, the Asian Indian community in the U.S. carries its own unique set of socio-cultural and immigration-related considerations that may influence impacts and prevalence rates of traumatic experiences. Examples of such socio-cultural and immigration-related considerations include prejudicial experiences, racial discrimination, and marginalization (e.g., anti-Muslim sentiment post 9/11, anti-Asian sentiment during the COVID-19 pandemic, “Dot Buster” incidents); stress due to the immigration process; economic stressors (e.g., financial responsibilities for accompanying families, need to send money to family in India); communication and language barriers; acculturation stressors (e.g., cultural shock); colonial mentality; stress due to ethnic identity conflicts; and the lack of knowledge about local healthcare institutions and policies (Chandra et al, 2016; Falicov et al, 2020; Inman, 2006; Inman, Yeh, et al, 2007; Jin et al, in press; Lee & Lu, 1989; Nadimpalli et al, 2016; Nikalje & Çiftçi, 2021; Tewari et al, 2003; Tummala-Narra & Deshpande, 2018; Tummala-Narra et al, 2011). Indeed, experiences of racism and discrimination contribute to poor psychological (Kaduvettoor-Davidson & Inman, 2013) and physical (Utsey et al, 2000) health.…”
Section: Traumatic Experiences and Posttraumatic Stress Disordermentioning
confidence: 99%
“…Specifically, Utsey et al found that Ghanaians tend to typically express CM in four ways: feelings of shame and inferiority, within-group discrimination, physical characteristics, and colonial debt. Similarly, Nikalje and Çiftçi (2021) found that Asian Indians tend to manifest CM as feeling ashamed and inferior for one's culture, preferring lighter skin color, discriminating against less-Americanized Indians (e.g., speaking with an Indian accent), and feeling indebted for colonization. Among Puerto Ricans, whose colonial experience is quite similar to that of Filipinos (Spanish and American colonialism), Capielo Rosario et al (2019) found that CM is commonly expressed through feelings of inferiority, shame, and embarrassment for being Puerto Rican, discriminating against less-Americanized Puerto Ricans, regarding European physical features as more desirable, and colonial debt.…”
Section: Manifestations Of Colonial Mentalitymentioning
confidence: 95%
“…They followed this up with the development of the Colonial Mentality Scale (CMS) for Filipino Americans (David & Okazaki, 2006b), which they hoped would spark more psychological research on CM not just among Filipinos but also among other communities with similar experiences of colonialism or oppression. Since then, the CMS has been adapted and used successfully among Ghanaians (Utsey et al, 2014), Puerto Ricans (Capielo Rosario et al, 2019, and Asian Indians (Nikalje & Çiftçi, 2021), making available psychometrically developed measures of CM for different social groups that, in turn, can stimulate even more research on this topic. Beyond the CMS, other literature on CM addresses it as experienced by Samoans (Faaleava, 2020), Mexicans (Miranda, 2011), and Peoples of Color in general (Hal, 2011).…”
Section: The Pervasiveness Of Colonial Mentalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its roots in Hinduism and British colonialism on the Indian subcontinent, research suggests that caste oppression persists transnationally in ethnically and religiously diverse South Asia and in the South Asian American diaspora (Gorur & Forscher, 2023;Thapa et al, 2021;Zwick-Maitreyi et al, 2018). This transmission of casteist beliefs may be conflated with cultural socialization about surnames, dietary practices, and parents' friendship and marriage preferences for their children (Gorur & Forscher, 2023;Nikalje & Çiftçi, 2023;Nikalje & Kumar, 2022;Sharma & Swami, 2022). Such possibilities underscore the importance of socializing critical consciousness, which can enable family members to understand the interplay between culture and systems of power and actively negotiate their compliance or opposition to oppressive intergenerational norms.…”
Section: Expanding Asian Americans' Racial-ethnic Socialization With ...mentioning
confidence: 99%